Cantharellus macrocarpus (Cantharellaceae, Cantharellales), a new species from tropical China - Zhang, Yu-Zhuo; Liang, Zhi-Qun; Xie, Hui-Jing; Wu, Lu-Ling; Xue, Rou; Zeng, Nian-Kai (Phytotaxa, 2021)
Cantharellus macrocarpus, a member of Cantharellus subgenus Cantharellus, is described as a new species from Hainan Province, China. It is characterized by large basidioma with a bright yellow-orange pileus and a well-developed, rugulose hymenophore, cream to pale yellowish stipe, noticeably thickened hyphal walls in the pileipellis, presence of clamp connections in all parts of the basidiomata, and a distribution in tropical Asia. A phylogenetic analysis of DNA sequences from part of the 28S gene and the translation elongation factor 1-a gene (TEF1) confirmed that it forms an independent lineage within subgenus Cantharellus. A detailed description, color photos of fresh basidiomata and line drawings of micromorphological features are presented.